Limits of the OFDM use in the radio mobile context. (2nd July 2019) - Boumediene, Fatima Zohra; Tayebi, Mohamed; Bouziani, Merahi
Orthogonal frequency division multiplexing (OFDM) is very vulnerable to the carrier frequency offset (CFO) generated mainly by the Doppler effect. The inter-carrier interference (ICI) generated by this offset degrades the system performances. Before stabilising its speed, a mobile must pass through a startup phase where the speed varies gradually in time. The same thing happens during a braking; the speed varies up to a zero value. In this paper, we investigate the effect induced by these speed variations on the OFDM system performances. The weight and the speed of the degradations are taken into account for further enhancement of the performances. The limits of the OFDM modulation are depicted in the line-of-sight (LOS) path where a mobile is subject to different types of accelerations. Simulation results show clearly the sensitivity of OFDM when mobile is subject to higher values of acceleration.